Core-Shell Structured PtRuCo x Nanoparticles on Carbon Nanotubes as Highly Active and Durable Electrocatalysts for Direct Methanol Fuel Cells - Cheng, Yi; Shen, P.; Saunders, M.; Jiang, San Ping (Elsevier Ltd, 2015)
Ternary alloy PtRuCox nanoparticles (NPs) with Co-rich core and PtRu skinned shell on carbon nanotubes (CNTs) have been successfully synthesized as electrocatalysts for methanol oxidation reaction (MOR) of direct methanol fuel cells (DMFCs) via a successive dealloying and annealing treatment of PtRuCo alloy particles. The best results were obtained on dealloyed PtRuCox NPs annealed at 450 °C in argon with x = 0.48, characterizing by a ~1 nm thick Co-free PtRu shell. The core–shell structured PtRuCox catalysts exhibit a high activity for MOR, 400 A g−1pt measured at 0.40 V (vs Ag/AgCl), almost 4 times higher than 104 A g−1Pt for the reaction on the PtRuCo alloy before deallaying and annealing treatment. The core–shell structured PtRuCox NPs also show excellent structural stability; maintaining 74% of the activity after 1000 cycle between −0.2 to 1.0 V (vs. Ag/AgCl), significantly higher than 49% for PtRuCo and 25% for the conventional PtRu/C catalysts. The results demonstrate that the successive dealloying and annealing treatment is very effective to synthesize core–shell structured PtRuCox ternary alloy electrocatalysts with high activity and durability for DMFCs.